The Love-Hate Relationship Between TGF-β Signaling and the Immune System During Development and Tumorigenesis - Chen, Baode; Mu, Chenglin; Zhang, Zhiwei; He, Xuelin; Liu, Xia (Frontiers in Immunology, 2022)
Since TGF-β was recognized as an essential secreted cytokine in embryogenesis and adult tissue homeostasis a decade ago, our knowledge of the role of TGF-β in mammalian development and disease, particularly cancer, has constantly been updated. Mounting evidence has confirmed that TGF-β is the principal regulator of the immune system, as deprivation of TGF-β signaling completely abrogates adaptive immunity. However, enhancing TGF-β signaling constrains the immune response through multiple mechanisms, including boosting Treg cell differentiation and inducing CD8+ T-cell apoptosis in the disease context. The love-hate relationship between TGF-β signaling and the immune system makes it challenging to develop effective monotherapies targeting TGF-β, especially for cancer treatment. Nonetheless, recent work on combination therapies of TGF-β inhibition and immunotherapy have provide insights into the development of TGF-β-targeted therapies, with favorable outcomes in patients with advanced cancer. Hence, we summarize the entanglement between TGF-β and the immune system in the developmental and tumor contexts and recent progress on hijacking crucial TGF-β signaling pathways as an emerging area of cancer therapy.